Signal properties study of neutron irradiated silicon photomultipliers down to 100 K - Currás-Rivera, E.; Blanc, F.; Haefeli, G.; Marchevski, R.; Ronchetti, F.; Schneider, O.; Shchutska, L.; Zunica, G. (Nuclear instruments & methods in physics research. Section A, Accelerators, spectrometers, detectors and associated equipment, 2026)
The LHCb experiment at CERN has been upgraded for the Run 3 operation of the Large Hadron Collider (LHC). A new concept of tracking detector based on Scintillating Fibres (SciFi) read out with multichannel silicon photomultipliers (SiPMs) was installed during its upgrade. One of the main challenges the SciFi tracker will face during its operation is the high radiation environment due to fast neutrons, where the SiPMs are located. In view of LHCb Upgrade II in 2033, the radiation levels will increase significantly, and the SciFi tracker must undergo a major upgrade. By the end of the lifetime, the expected radiation fluence will reach 3.0×1012neqcm−2 at the SiPMs’ location. To cope with the increase in radiation, cryogenic cooling with liquid nitrogen is being investigated as a possible solution to mitigate the performance degradation of the SiPMs induced by radiation damage. Thus, a detailed performance study of different layouts of SiPM modules produced by FBK and Hamamatsu is being carried out. These detectors have been designed to operate at cryogenic temperatures. Several detectors were irradiated with different neutron fluences and tested in a dedicated cryogenic setup down to 100K. Key performance parameters, such as breakdown voltage, quenching resistor value, recovery time, and pulse amplitude, are characterized as a function of temperature and neutron fluence. Also, the forward voltage diode as a function of temperature was measured, and the silicon energy bandgap was estimated. The main results of this study are going to be presented here.